The Role of Collaborative Student Research on the Development of 21st Century Skills. Issue 1657 (29th April 2014) - Day, Deborah A; Ferrari, Nicole; Broadbridge, Christine C.
ABSTRACT: Collaborative student research takes place in educational settings where the teacher directs the laboratory (traditional class) or allows the students to research a topic (non-traditional class). This study examines the role of collaborative student research in two separate settings: in high school (grades 9-12) and in college undergraduate institutions. These experiences include college level Research Experiences for Undergraduates (REU) and high school level Authentic Science Research (ASR) programs. These programs promote collaboration among student peers, teachers, professors, graduate students, post-docs, community members, and industry experts. Benefits of these collaborative student research programs may include development of skills aligned with educational standards such as Common Core State Standards and the Next Generation Science Standards. This study examines the short and long-term outcome of student engagement in collaborative student research experiences, and offers new insight regarding the impact that these unique experiences have on 21st century skill development. Students in this study have participated in non-traditional, research-based experiences ranging from 8 weeks to 4 years. Pre-post and retrospective student survey data was examined qualitatively and quantitatively to better understand the role in which collaborative student research experiences play in the formation of 21st century skills. Results of the study support the notion that collaborative student research experiences offer students meaningful interdisciplinary benefits, and these experiences are more than just a means of recruiting students into science, technology, engineering and math (STEM) fields.